Improving The Quality of Teacher Services Through Teacher Personality Development and Organizational Justice - Siregar, Uli Rohana; Hermawan, Andi (Dinasti Publisher, 2026)
The quality of teacher service is an important element related to achieving national education goals and developing the whole Indonesian person. The initial survey of the quality of service of Civil Servant teachers in Senior High Schools in Bogor Regency has not achieved optimal results. Therefore, the quality of teacher service is interesting to study. This study aims to find efforts on how the quality of teacher service can be improved by examining the relationship between the quality of teacher service and the variables of teacher personality and organizational justice. The study used correlational statistical methods, and a SITOREM method analysis was conducted. The research analysis unit was Civil Servant teachers in Senior High Schools with a population of 279 and a sample of 103 teachers. The results of the study showed a positive relationship between teacher personality and the quality of teacher service, with a relationship strength of ry1 = 0.421 and there was a positive relationship between organizational justice and the quality of teacher service, with a relationship strength of ry2 = 0.297, so that the quality of teacher service can be improved through teacher personality and organizational justice. It can be concluded that to improve the quality of teacher service, one can pay attention to indicators that are not yet optimal for recommendations and determine the priority order of improvements that need to be made.